The Development of Hotel Restaurant Glossary Cards for Kindergarten Students of Fatimah 7 Palembang - Sandira, Rara; Lestari, Pratiwi; Yusri, Yusri; Rohliah, Leni (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2024)
Vocabulary mastery or glossary for children is necessary in learning English because a good understanding of vocabulary will support the ability to master English skills. Card media is one of the print learning media that can be used by children to master vocabulary quickly. The purpose of this study was to determine the form of development of hotel restaurant glossary cards for Fatimah 7 Palembang Kindergarten students. This study was conducted using the Research & Development approach developed by Plomp (1997) with the stages of preliminary investigation, designing, realization/construction, testing, evaluation, and revision, and implementation. Data was collected through interviews. The study was conducted in July-November 2023 with the population and sample of Fatimah 7 Palembang Kindergarten students. The final product was glossary cards that had been tested and validated by experts of linguistic, content and design. This study produced product outputs in the form of a final report, SINTA accredited scientific articles, and Hotel Restaurant Glossary Cards products registered in HKI.